Beyond compost: Using urban biowaste derived compost to produce new fertilizing products - Machado, Telmo (2022)
The agro-food sector is a contributor to CO2 emissions and polluter due to its difficulty to deal with waste generation. Using the farm to fork concept we can observe that waste is produced in every link of the food value chain. Nevertheless, efforts are being made worldwide to reduce its environmental impact - from producing food with precision agriculture to sustainable food packaging systems – hoping to influence the way each country manages its biowaste. In this work we present the first results of an experiment, conducted under the project “BIOMA – Bioeconomy integrated solutions for the mobilization of the Agro-food market”, to produce a Urban waste compost based plant biostimulant.